2016
DOI: 10.3839/jabc.2016.003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Biological Degradation Cypermethrin by Bacillus amyloliquefaciens AP01

Abstract: Strain AP01 was isolated for the biological cypermethrin degradation from soil and sediment in Busan. This strain was identified on the basis of phylogenetic analysis of the 16s rDNA sequence and assigned as Bacillus amyloliquefaciens AP01. AP01 could degrade about 45% of cypermethrin in the mineral medium at 30 o C and 180 rpm for 5 days. Furthermore when 2% glucose was added in the medium, the degradation rate of cypermethrin by strain AP01 was increased upto about 60%. Therefore, AP01 may serve as a promisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Furthermore, the influence of B. amyloliquefaciens on the degradation of other pesticides was studied. Lee et al (2016) demonstrated the cypermethrin degradation at a level of 45% in 5 days, using the B. amyloliquefaciens APO1 strain in the mineral medium. Furthermore, when 2% glucose was added to the medium, the rate of cypermethrin degradation by the AP01 strain increased to about 60%.…”
Section: Reviewmentioning
confidence: 92%
“…Furthermore, the influence of B. amyloliquefaciens on the degradation of other pesticides was studied. Lee et al (2016) demonstrated the cypermethrin degradation at a level of 45% in 5 days, using the B. amyloliquefaciens APO1 strain in the mineral medium. Furthermore, when 2% glucose was added to the medium, the rate of cypermethrin degradation by the AP01 strain increased to about 60%.…”
Section: Reviewmentioning
confidence: 92%
“…Contaminated sites are considered to be a good source for the isolation of pyrethroid-degrading microorganisms (Tables 3 , 4 ). Using enrichment culture techniques, several bacterial and fungal species belonging to various genera have been isolated from pyrethroid-contaminated soils (Wang et al, 2011 ; Cycoń et al, 2014 ; Akbar et al, 2015a ; Bhatt et al, 2016 ; Lee et al, 2016 ), sludge (Yuanfan et al, 2010 ; Chen et al, 2011a ; Sundaram et al, 2013 ; Xiao et al, 2015 ; Tiwary and Dubey, 2016 ), or wastewater (Lin et al, 2011 ; Zhang S. et al, 2011 ; Chen et al, 2014 ). For the effective use of microorganisms in the remediation of pyrethroid-contaminated soils, it is extremely important to determine the potential of these microorganisms for the degradation of pyrethroids under optimal conditions in liquid media.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed that several bacterial (Table 3 ) and fungal (Table 4 ) species are capable of degrading pyrethroids in liquid cultures. As is illustrated in these tables, microorganisms can degrade pyrethroids by either using them directly as a source of carbon (e.g., Paingankar et al, 2005 ; Chen et al, 2014 ; Cycoń et al, 2014 ; Liu et al, 2014 ; Akbar et al, 2015b ) or co-metabolically (e.g., Saikia and Gopal, 2004 ; Chen et al, 2011a ; Zhang S. et al, 2011 ; Lee et al, 2016 ). However, the rate of the biodegradation process in liquid media is influenced by many factors including temperature, pH, nutrients, pyrethroid concentration, inoculum size as well as the properties of the bacterial or fungal strains (Saikia and Gopal, 2004 ; Zhang et al, 2010 ; Zhao et al, 2013 ; Chen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also pyrethroid degrading Cladosporium sp. HU (Chen et al, 2011a), S. aureus HP-S-01 (Chen et al, 2011c) and Bacillus amyloliquefaciens AP01 (Lee et al, 2016) have shown positive response to the addition of carbon source. Here, the growth rate of the pyrethroid degrading bacteria was Fig.…”
Section: Optimisation Of Conditions For Cyfluthrin Degradationmentioning
confidence: 99%